PIK3CA mutations predict recurrence in localized microsatellite stable colon cancer. (2nd February 2015) - Manceau, Gilles; Marisa, Laetitia; Boige, Valérie; Duval, Alex; Gaub, Marie‐Pierre; Milano, Gérard; Selves, Janick; Olschwang, Sylviane; Jooste, Valérie; le Legrain, Michè; Lecorre, Delphine; Guenot, Dominique; et al.
Abstract : By using fresh frozen tissue samples from two large independent cohorts with a total of 826 stage I–III colon cancers (CCs), we found that patients with PIK 3 CA ‐mutated microsatellite stable tumors experienced a significant increased 5‐year relapse‐free survival and overall survival compared with those without PIK 3 CA mutation. Our study suggests that PIK 3 CA mutations could be used as a favorable prognostic biomarker in the adjuvant setting for CC. Abstract: PIK3CA, which encodes the p110 α catalytic subunit of PI3K α, is one of the most frequently altered oncogenes in colon cancer (CC), but its prognostic value is still a matter of debate. Few reports have addressed the association between PIK3CA mutations and survival and their results are controversial. In the present study, we aimed to clarify the prognostic impact of PIK3CA mutations in stage I–III CC according to mismatch repair status. Fresh frozen tissue samples from two independent cohorts with a total of 826 patients who underwent curative surgical resection of CC were analyzed for microsatellite instability and screened for activating point mutations in exon 9 and 20 of PIK3CA by direct sequencing. Overall, 693 tumors (84%) exhibited microsatellite stability (MSS) and 113 samples (14%) harbored PIK3CA mutation. In the retrospective training cohort ( n  = 433), patients with PIK3CA ‐mutated MSS tumors ( n  = 47) experienced a significant increased 5‐year relapse‐free interval compared with PIK3CA wild‐type MSS tumors ( n  = 319) in univariate analysis (94% vs. 68%, Log‐rank P  = 0. 0003) and in multivariate analysis (HR = 0.12; 95% confidence interval, 0.029–0.48; P  = 0.0027). In the prospective validation cohort ( n  = 393), the favorable prognostic impact of PIK3CA mutations in MSS tumors ( n  = 327) was confirmed (83% vs. 67%, Log‐rank P  = 0.04). Our study showed that PIK3CA mutations are associated with a good prognosis in patients with MSS stage I–III CC.